Genetics and the Family Environment - Eley, T; Lau, J (Elsevier, 2005)
The chapter offers some insight into the valuable contribution made by behavioral genetics to the understanding of the family environment. A powerful behavioral genetic tool for examining purely nonshared environmental impact of specific measured aspects of the environment is the MZ differences design. The strength of this design lies in the fact that, like the adoption design, it can give one a clean estimate of one type of effect-nonshared environment. The extent to which MZ twins differ on behavioral and emotional ratings is assumed to be because of nonshared environment only. An adoption research that considered the role of both gene-environment correlation and interaction found that exposure to adversity in the life of the adoptive parents moderated the effects of genetic risk on the child's environment. Information on parental antisocial behavior, child conduct problems, and the degree of father presence in the family home was collated, and used in a regression framework that had traditionally been designed to assess the effects of genetic and shared environmental variance. © 2005 Elsevier Ltd. All rights reserved.